Biostimulant Effects of Trichoderma asperellum in Hydroponic Spinach Production - Jared Hernández-Huerta; Brenda I. Guerrero; Angélica Anahí Acevedo-Barrera; Martha Irma Balandrán-Valladares; Rosa María Yañez-Muñoz; Ndahita De Dios-Avila; Aldo Gutiérrez-Chávez (Life)
Using beneficial microorganisms as biostimulants is a promising strategy to enhance crop growth and productivity in hydroponic systems. Trichoderma asperellum has demonstrated plant growth-promoting effects in soil cultivation; however, its efficacy in hydroponic Deep-Water Culture (DWC) systems remains underexplored. This research evaluated the effect of T. asperellum strains TaMFP1 and TaMFP2 on the growth, nutrient uptake, and visual quality of hydroponically grown spinach cv. Stella Plus F-1 (Spinacia oleracea L.). A randomized complete design was used, comparing inoculated plants with a control and a commercial Trichoderma harzianum product. After 28 days, the results showed that T. asperellum significantly increased plant height (23.1%), collar diameter (21.8%), root length (39.6%), leaf area (22.0%), number of leaves (18.05), and fresh biomass accumulation (23.5%) compared to non-inoculated plants. Furthermore, inoculation with TaMFP1 improved spinach yield by 34.5%, while nutrient analysis indicated enhanced phosphorus and calcium uptake. No significant changes were observed in photosynthetic pigment concentrations, and the visual quality of the harvested spinach was unaffected. These findings highlight the potential of T. asperellum as a sustainable biostimulant in hydroponic spinach production. These results contribute to developing beneficial microorganism-based strategies to enhance the sustainability of hydroponic agriculture.